Scanning electron microscopy of third-instar sarcophagid (Diptera: Sarcophagidae) recovered from a mummified human corpse in Thailand - Sukontason K. (2014)
The third-instar of an unidentified sarcophagid, recovered from a mummified body of a 32-yr-old Thai male was examined using scanning electron microscopy (SEM). Although the morphological features of this larva are similar to the other sarcophagid larvae, some features could be helpful for species identification, which is a basic requirement for estimation of postmortem interval in forensic investigation. These features included number and arrangement of papillae on the anterior spiracle, structure of spines, size of circumspiracular tubercles at caudal segment and branching peculiarity of the posterior spiracular hairs. This information could benefit future identification of the sarcophagid larvae that exist in Thailand.